Audit Komunikasi Internal - Andre Hardjana (Jurnal InterAct, 2014)
This article argues that internal communication has two functions, namely as channels for sharing task information and creating an organizational climate conducive for trusting relations. As an essential part of an organizational communication system, internal communication is central to organizational success. In a changing environment, however, its effectiveness is subject to severe pressures of internal and external forces. A regular assessment is needed to keep internal communication effective. The best way to assess it is by undertaking communication audit, in which the results can be used by communication specialists to design the right program for improving the organization’s  communication system.